Enabling room-temperature processed highly efficient and stable 2D Ruddlesden–Popper perovskite solar cells with eliminated hysteresis by synergistic exploitation of additives and solvents. Issue 5 (18th January 2019) - Yu, Shuang; Yan, Yajie; Chen, Yani; Chábera, Pavel; Zheng, Kaibo; Liang, Ziqi
Abstract : In 2D RP perovskites, two competitive processes of NH4 Cl and DMSO additions reach a delicate balance in dual-treated devices, which deliver a maximum PCE up to 13.41% with excellent air-stability and eliminated hysteresis. Abstract : Herein we demonstrate the favorable synergistic effect of an NH4 Cl additive and DMSO solvent on 2D perovskites that are synthesized at room temperature. Interestingly, we observe the spontaneous formation of 3D phases within either NH4 Cl or DMSO treated 2D perovskites, which plays a pivotal role in facilitating charge transport. It is revealed that NH4 Cl increases charge carrier lifetime and passivate trap states within the 3D phase while DMSO promotes 2D/3D inter-phase charge transfer. These two competitive processes reach a delicate balance in DMSO and NH4 Cl co-treated devices, which deliver a maximum PCE up to 13.41% with excellent air-stability and eliminated hysteresis. This is among the highest values reported for 2D RP perovskite ( n = 4) based planar solar cells, particularly via all low-temperature solution fabrication.